2011
DOI: 10.1111/j.1745-4530.2009.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN MUSCLE PROPERTIES DURING POSTMORTEM STORAGE OF FARMED SEA BREAM (SPARUS AURATA)

Abstract: This study assesses the effects of storage temperature on postmortem changes in textural parameters (firmness, water holding capacity), and their relationship with biochemical and electrophoretic determinations (muscle collagen content and solubility, amount and integrity of sarcoplasmic and myofibrillar proteins) in sea bream muscle. Storage at 1C resulted in a prolongation of the firmness compared with 4C, with no noticeable changes in water holding capacity. This delay in muscle softening at 1C could be par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…[21] An increase of WHC was observed during the first 4 h at 0 • C, and then decreased from 67.27% at 4 h to 49.42% at 72 h. According to Nguyen et al, [22] the decreased WHC was probably due to the water loss from muscle fiber driven by protein denaturation. The result also indicated that the change of WHC within postmortem process was in accordance with the change of texture parameters ( Table 1).…”
Section: Change In Texture Parameters Early Post-mortem Timementioning
confidence: 93%
See 2 more Smart Citations
“…[21] An increase of WHC was observed during the first 4 h at 0 • C, and then decreased from 67.27% at 4 h to 49.42% at 72 h. According to Nguyen et al, [22] the decreased WHC was probably due to the water loss from muscle fiber driven by protein denaturation. The result also indicated that the change of WHC within postmortem process was in accordance with the change of texture parameters ( Table 1).…”
Section: Change In Texture Parameters Early Post-mortem Timementioning
confidence: 93%
“…A large variation in the biochemical process was observed during rigor period. [21] The progressive denaturation and hydrolysis of myofibrillar proteins had a negative effect on the toughness of post-mortem fish. Therefore, rigor mortis process affected the texture such as hardness, gumminess, springiness, cohesiveness and resilience (Table 1).…”
Section: Change In Texture Parameters Early Post-mortem Timementioning
confidence: 99%
See 1 more Smart Citation
“…Water holding capacity (WHC) was determined according to Suárez et al . () with some modifications. A fish sample (2 g) was placed in a centrifuge tube that contained tissue paper to absorb water and then centrifuged for 10 min at 1590 × g .…”
Section: Methodsmentioning
confidence: 99%
“…2005). Suárez et al . (2005, 2009) reported that initial total collagen content, acid‐soluble collagen (ASC) and insoluble collagen (ISC) of sea bream decreased throughout the storage period at 4C and 1C, and storage at 1C kept the initial amount of ASC and ISC for a longer period than storage at 4C.…”
Section: Discussionmentioning
confidence: 99%